A Comprehensive Review on Dry Eye Disease: Diagnosis, Medical Management, Recent Developments, and Future Challenges. (28th January 2015) - Phadatare, Suvarna P.; Momin, Munira; Nighojkar, Premanand; Askarkar, Sonali; Singh, Kamalinder K.
Abstract : Dry eye syndrome (DES) or keratoconjunctivitis sicca (KCS) is a common disorder of the tear film caused by decreased tear production or increased evaporation and manifests with a wide variety of signs and symptoms. The present review from interpretation of the literature gives detailed information on the prevalence, definition, causes, diagnostic tests, and medical management of dry eye disease. A number of systems contribute to the physiological integrity of the ocular surface and disruption of system may or may not produce symptoms. Therefore accurate diagnosis of dry eyes with no or minimal disruption of physiological function is necessary. The paper also discusses different colloidal drug delivery systems and current challenges in the development of topical ophthalmic drug delivery systems for treatment of KCS. Due to the wide prevalence and number of factors involved, newer, more sensitive diagnostic techniques and novel therapeutic agents have been developed to provide ocular delivery systems with high therapeutic efficacy. The aim of this review is to provide awareness among the patients, health care professionals, and researchers about diagnosis and treatment of KCS and recent developments and future challenges in management of dry eye disease.